Adjustment of peak streamflows of a tropical river for urbanization - Amini, Ata; Mohammed Ali, Thamer Ahmed; Ghazali, Abdul Halim; Kim Huat, Bujang (Science Publications, 2009)
Peak runoff from a catchment is influenced by many factors such as intensity and duration of rainfall, catchment topography, catchment shape, land use and other variables. For a particular catchment, landuse change and other human activities will alter the characteristic of catchment hydrograph. Problem statement: As a result of urbanization, the magnitude of floods occurring in a catchment increased. It was found that the land use change in the Langat River catchment has clear impact on annual peak streamflow record, particularly from 1983-2003 while, the change has no significant impact on streamflow record from 1960-1982. Spatial data confirms the heavy development occurred in river basin from 1983-2003. Thus, urbanization makes the historical record of Langat River non-homogenous and this makes the mathematical simulation for the record inappropriate due to poor expected output. Approach: In this study, historical record of Langat River, Selangor, Malaysia from 1960-2003 was used to study the impact of urbanization on the streamflow. The annual peak streamflow was selected for this purpose. The peak streamflow record was divided into two sets. Set one from 1960-1982 and set two from 1983-2003, which represent periods before and after urbanization, respectively. To adjust the set one data for urbanization, different adjustment factors were used to make the data homogeneous. Normal model was applied to find the best factor for model fitness. Results: The best adjustment factors were selected by trial and error technique based on 95% confidence level. To determine the optimum adjustment factors from the best ones, the point of intersection between the homogeneity and Normal model evaluation curves was located. This point represented the optimum adjustment factor and its value was found to be 1.9. Autorun model was used to validate the above finding and it was found that the model prediction is acceptable with reasonable accuracy. Conclusion/Recommendations: The proposed method can be recommended to be used for predicting the streamflow of Langat River considering the impact of urbanization on the streamflow. The method also, is applicable to adjust a flood record for which flood events had occurred on a watershed undergoing continuous changes in levels of urbanization to meet both homogeneity and best model fitness.